Rozwój Narcissus poeticus L. [Development of Narcissus poeticus L.] - B. Jamiołowska (Acta Agrobotanica, 2015)
One generation of Narcissus poeticus develops during three seasons. The vegetative stage of the meristem lasts 11 months. It changes to a floral apex in the second year and initiates all the flower elements from the first days of June to mid August. The plants bloom in the third year.